A Platinum Cantilever-Based Thermal Conductivity Detector for Ammonia Sensing Using the 3-Omega Technique. (1st January 2019) - Lotfi, Ardalan; Navaei, Milad; Hesketh, Peter J.
Abstract : In this work, the effect of gap size on a TCD sensor performance was studied through a comprehensive COMSOL model to test an optimal geometric design. The platinum cantilever-based thermal conductivity was designed and fabricated to satisfy the demands for the 3-omega technique thermal stresses as well as provide stability for corrosive gases such as ammonia. The fabricated sensor in this process was capable of detecting 30 ppm ammonia gas in helium. The effects of temperature and humidity change were also explored to establish a function to compensate for environmental variations.